Pemanfatan Temu Mangga dan Sambiloto untuk Imunitas Tubuh - Pujimulyani, Dwiyati; Suryani, Chatarina Lilis; Astuti, Devi Fitri; Saputra, Jumadil (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2023)
Indonesia is located on the equator with a rich potential of local spices, for example, white turmeric of Curcuma Mangga (Curcuma mangga Val.) and Sambiloto leaves (Andrographis paniculata). These two food ingredients are only sold in fresh form because some people do not know how to process them properly and practically. Curcuma mangga can be processed into instant, ready-to-drink powder that is easy to consume. Not only that but curcuma mangga and sambiloto leaves also contain antioxidants such as polyphenols, which can be useful for increasing immune power. The purpose of this service is for partners to understand the benefits of Curcuma Mangga and Sambiloto leaves. The outreach activity was held on November 23, 2022, and was attended by 21 Himatepa-HMPPI UMBY administrators and 54 NREC Universiti Malaysia Terengganu. This activity includes counseling and training about the benefits of Curcuma Mangga and Sambiloto leaves and how to market them. The counseling also discussed how to process instant powder and Sambiloto. This service program resulted in partners understanding the benefits of Curcuma Mangga and Sambiloto leaves to increase immunity and its marketing strategies. The panelists liked the overall instant mango powder product with a score of 3.95. Partners can also increase their entrepreneurial abilities by producing instant powder from Curcuma Mangga and Sambiloto.